The Interactions Between Sediments and Water - Kronvang, Brian; Faganeli, Jadran; Ogrinc, Nives (Springer Netherlands : Imprint: Springer, 2006)
This book focuses on sediments as a pollutant in natural freshwater and marine habitats, and as a vector for the transfer of chemicals such as nutrients and contaminants. Sediment-water research is carried out all over the world within a variety of disciplines. The selected papers cover three main topics: -assessment and/or restoration of disturbed watersheds -sediment-water linkages in terrestrial and aquatic environments -evaluation of sediment and ecological changes in marine and freshwater habitats Innovative research in both developed and less developed countries is included and both fundamental research and insight into applied research and system management are covered. This book will be of interest to graduate students, researchers, catchment managers and government regulators working within many areas of education, protection and management of the environment, including sediment geochemistry and dynamics, aquatic habitats, water quality, aquatic ecology, river morphology, restoration techniques and catchment management. Reprinted from Water, Air, & Soil Pollution: Focus, Volume 6, Issues 5-6, 2006.